Geodetic Constraints of the 2017 Mw7.3 Sarpol Zahab, Iran Earthquake, and Its Implications on the Structure and Mechanics of the Northwest Zagros Thrust‐Fold Belt. Issue 14 (19th July 2018) - Feng, Wanpeng; Samsonov, Sergey; Almeida, Rafael; Yassaghi, Ali; Li, Junhua; Qiu, Qiang; Li, Peng; Zheng, Wenjun
Abstract: We reveal transient surface deformation following the 2017 Mw 7.3 Sarpol Zahab (Iran) earthquake using Interferometric Synthetic Aperture Radar (InSAR) measurements. Based on the coseismic interferograms derived from the Advanced Land Observing Satellite‐2 (ALOS‐2) data, the preferred slip model of the earthquake has a centroid depth of 14.5 ± 4 km and suggests that a basement fault is most likely responsible for the 2017 earthquake in the northwest Zagros fold‐thrust belt zone. Two slip asperities with a maximum slip of 6 m separated by 16 km are observed in the best fitting slip model. The accumulated afterslip in the first month after the mainshock determined from the Sentinel‐1 postseismic interferograms reveals a slip distribution that lies immediately updip of the coseismic slip, implying that frictional properties of the fault vary along the rupture patch. The Bamo Mount in the earthquake area was uplifted by approximately 1 m during the earthquake. We suggest that local topographic growth from both seismic and aseismic faulting behaviors is common within the Zagros fold‐thrust belt zone based on our findings regarding the 2017 earthquake and other significant events in the region. Key Points: We propose that a basement fault at a depth of 15 km in the northwest Zagros folded belt zone is responsible for the strongest earthquake instrumentally recorded in the Iran‐Iraq border region, the 2017 Mw 7.3 Sarpol Zahab earthquake Two asperities with a maximum slip of 6 m in the 2017 Mw 7.3 Sarpol Zahab earthquake were revealed with InSAR observations Frictional properties of the earthquake fault vary in the rupture area